Treading water: Coping with uncertainty during a novel pandemic - Sachin Patel (The Beryl Institute, 2020)
The abruptness with which the COVID-19 pandemic has changed the delivery of healthcare will have a lasting effect on patients and families of intensive care unit survivors. Using the best science and epidemiology healthcare systems developed protocols and policies to implement the highest level of care but mitigate disease spread. Out of these initiatives the "no visitor" policy was born. The impact of COVID-19 causing florid respiratory failure immediately derailed the lives of a happily retired couple. While on mechanical ventilation for sixteen days, Betty was unable to connect with her husband of over 40 years. In that time, the critical care team became familiar with techniques to treat COVID patients all the while understanding that self-care will be vital in preventing burnout during this pandemic. The balance between reducing the spread of a pathogen and giving our patients and families a human connection will be an on-going challenge in the months ahead. Experience Framework This article is associated with the Staff & Provider Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Staff%20%26%20Provider%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.